2021
DOI: 10.1038/s41591-021-01513-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and antiviral activity of the antisense oligonucleotide bepirovirsen in patients with chronic hepatitis B: a phase 2 randomized controlled trial

Abstract: Chronic infection with hepatitis B virus (HBV) leads to an increased risk of death from cirrhosis and hepatocellular carcinoma. Functional cure rates are low with current treatment options (nucleos(t)ide analogs (NAs) and pegylated interferons). Bepirovirsen is an antisense oligonucleotide targeting all HBV messenger RNAs; in cell culture and animal models, bepirovirsen leads to reductions in HBV-derived RNAs, HBV DNA and viral proteins. This phase 2 double-blinded, randomized, placebo-controlled trial is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 26 publications
0
59
2
Order By: Relevance
“…The main concerns regarding these agents include the risk of off-target toxicity, the potential toxicity of the delivery vehicle, and the risk of post-treatment reactivation by remaining cccDNA [ 219 ]. In addition, ALT flare should be monitored during the course of the treatment [ 224 ].…”
Section: New Drugs For a Functional Curementioning
confidence: 99%
“…The main concerns regarding these agents include the risk of off-target toxicity, the potential toxicity of the delivery vehicle, and the risk of post-treatment reactivation by remaining cccDNA [ 219 ]. In addition, ALT flare should be monitored during the course of the treatment [ 224 ].…”
Section: New Drugs For a Functional Curementioning
confidence: 99%
“…Finally, bepirovirsen, an antisense oligonucleotide, was recently reported to inhibit HBV infection by targeting all HBV messenger RNAs. The results of a recent phase 2 randomized controlled trial of this drug showed that it performed with gratifying efficacy and a favorable safety profile ( Yuen et al, 2021 ). Combining viral entry and replication inhibition will likely benefit the development of curative strategies for patients with chronic HBV.…”
Section: Discussionmentioning
confidence: 99%
“…assessed the safety, tolerability, and antiviral activity of the ASO, bepirovirsen, in a phase 2 randomized double-blinded, placebo-controlled, dose escalation trial. 1 The binding site of bepirovirsen is present in all HBV mRNA, and is thus anticipated to attenuate all HBV mRNA’s including pre-genomic RNA. 3 This study included treatment-naive and experienced, non-cirrhotic patients, where 2 subcutaneous injection doses of bepirovirsen, 150 mg and 300 mg, were tested.…”
Section: Main Textmentioning
confidence: 99%
“…Yuen et al. 1 report on the safety and antiviral efficacy of this agent. We “spotlight” key findings of this study and its impact for future clinical trial design.…”
mentioning
confidence: 99%